Inflammatory infiltrates in parathyroid tumors. Issue 6 (December 2017) - Haglund, Felix; Hallström, Björn M; Nilsson, Inga-Lena; Höög, Anders; Juhlin, C Christofer; Larsson, Catharina
Abstract : Context: Inflammatory infiltrates are sometimes present in solid tumors and may be coupled to clinical behavior or etiology. Infectious viruses contribute to tumorigenesis in a significant fraction of human neoplasias. Objective: Characterize inflammatory infiltrates and possible viral transcription in primary hyperparathyroidism. Design: From the period 2007 to 2016, a total of 55 parathyroid tumors (51 adenomas and 4 hyperplasias) with prominent inflammatory infiltrates were identified from more than 2000 parathyroid tumors in the pathology archives, and investigated by immunohistochemistry for CD4, CD8, CD20 and CD45 and scored as +0, +1 or +2. Clinicopathological data were compared to 142 parathyroid adenomas without histological evidence of inflammation. Transcriptome sequencing was performed for 13 parathyroid tumors (four inflammatory, 9 non-inflammatory) to identify potential viral transcripts. Results: Tumors had prominent germinal center-like nodular (+2) lymphocytic infiltrates consisting of T and B lymphocytes (31%) and/or diffuse (+1–2) infiltrates of predominantly CD8+ T lymphocytes (84%). In the majority of cases with adjacent normal parathyroid tissue, the normal rim was unaffected by the inflammatory infiltrates (96%). Presence of inflammatory infiltrates was associated with higher levels of serum-PTH ( P = 0.007) and oxyphilic differentiation ( P = 0.002). Co-existent autoimmune disease was observed in 27% of patients with inflammatory infiltrates, which in turn was associated with oxyphilic differentiation ( P = 0.041). Additionally, prescription of anti-inflammatory drugs was associated with lower serum ionized calcium ( P = 0.037). Conclusions: No evidence of virus-like sequences in the parathyroid tumors could be found by transcriptome sequencing, suggesting that other factors may contribute to attract the immune system to the parathyroid tumor tissue.